2022
DOI: 10.3389/fmolb.2022.1019290
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS profiling of volatile metabolites produced by Klebsiella pneumoniae

Abstract: Currently used methods for diagnosing ventilator-associated pneumonia (VAP) are complex, time-consuming and require invasive procedures while empirical antibacterial therapy applies broad spectrum antibiotics that may promote antimicrobial resistance. Hence, novel and fast methods based on alternative markers are needed for VAP detection and differentiation of causative pathogens. Pathogenic bacteria produce a broad range of volatile organic compounds (VOCs), some of which may potentially serve as biomarkers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…In recent years, VOCs have been increasingly utilized for strain characterization (Drees et al 2019 ; Kunze et al 2013 ; Lu et al 2022 ). In addition, it is possible to differentiate CRKP and CSKP in TSB media using changes in VOCs (Filipiak et al 2022 ). Nevertheless, we note that there are few studies employing commercial BC bottles emitting VOCs to identify CRKP and determine its CBPM phenotype, further emphasizing the strengths of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, VOCs have been increasingly utilized for strain characterization (Drees et al 2019 ; Kunze et al 2013 ; Lu et al 2022 ). In addition, it is possible to differentiate CRKP and CSKP in TSB media using changes in VOCs (Filipiak et al 2022 ). Nevertheless, we note that there are few studies employing commercial BC bottles emitting VOCs to identify CRKP and determine its CBPM phenotype, further emphasizing the strengths of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a correlation between the growth metabolism of K . pneumoniae and VOCs, including propionic acid (BCs) (Julak et al 2000 ), acetic acid (BCs/LB) (Julak et al 2000 ), 3-methyl-1-butanol (sheep blood agar/TSB/LB) (Filipiak et al 2022 ; Junger et al 2012 ; Luo et al 2023 ), butane-2,3-dione (diacetyl) (TSB) (Filipiak et al 2022 ), and 3-hydroxy-2-butanone (malt extract agar and dichloran glycerol agar/TSB supplemented with 5% hemolyzed human blood) (Kiviranta et al 1998 ; Rees et al 2016 ). These findings align with the outcomes of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzene is a possible marker for lung carcinoma [58] and 2-nonanone is a possible marker for bacterial infections, especially Pseudomonas aeruginosa and Staph aureus [59] and Klebsiella pneumoniae [60] were also detectable in room air. If only their concentration in exhaled air is considered, inhalation exposure to these markers would be ignored.…”
Section: Runmentioning
confidence: 99%
“…Gas chromatography combined with mass spectrometry (GC–MS) is usually used to analyze the volatile metabolome ( Filipiak et al, 2022 ). Composition of SCFAs in stool samples are well described but most of the published data were obtained by the solid phase microextraction method (SPME) ( Marrubini et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%